The custom of the castle : from Malory to Macbeth - Ross, Charles Stanley (University of California Press, 1997)
This title is part of UC Press's Voices Revived program, which commemorates University of California Press's mission to seek out and cultivate the brightest minds and give them voice, reach, and impact. Drawing on a backlist dating to 1893, Voices Revived makes high-quality, peer-reviewed scholarship accessible once again using print-on-demand technology. This title was originally published in 1997.
Keywords: Shakespeare, William, -- 1564-1616 -- Knowledge -- Social life and customs.; Malory, Thomas, -- Sir, -- active 15th century. -- Morte d'Arthur.; Spenser, Edmund, -- 1552?-1599. -- Faerie queene.; Shakespeare, William, -- 1564-1616; Faerie queene (Spenser, Edmund); Morte d'Arthur (Malory, Thomas, Sir); English literature -- Early modern, 1500-1700 -- History and criticism.; Castles in literature.; English literature -- European influences.; Knights and knighthood in literature.; Manners and customs in literature.; Kings and rulers in literature.; Literature and society.; Society in literature.; Châteaux dans la littérature.; Mœurs et coutumes dans la littérature.; Rois et souverains dans la littérature.; Littérature et société.; BIOGRAPHY & AUTOBIOGRAPHY -- Literary.; Society in literature; Castles in literature; English literature -- Early modern; English literature -- European influences; Kings and rulers in literature; Knights and knighthood in literature; Literature and society; Manners and customs in literature; 1500-1700; Criticism, interpretation, etc.